Evaluation of the Hypoglycemic Activity of Morchella conica by Targeting Protein Tyrosine Phosphatase 1B - Naeema Begum; Abdul Nasir; Abdul Nasir; Zahida Parveen; Taj Muhammad; Asma Ahmed; Saira Farman; Nargis Jamila; Mohib Shah; Noor Shad Bibi; Akif Khurshid; Zille Huma; et al. (Frontiers Media S.A., 2021)
Morchella conica (M. conica) Pers. is one of six wild edible mushrooms that are widely used by Asian and European countries for their nutritional value. The present study assessed the anti-diabetic potential of M. conica methanolic extract (100 mg/kg body weight) on streptozotocin (STZ)-induced diabetic mice. STZ was used in a single dose of 65 mg/kg to establish diabetic models. Body weights, water/food intake and fasting blood glucose levels were measured. Histopathological analysis of the pancreas and liver were performed to evaluate STZ-induced tissue injuries. In addition, in vitro assays such as α-amylase and protein tyrosine phosphatase 1B (PTP1B) inhibitory, antiglycation, antioxidant and cytotoxicity were performed. The in vitro study indicated potent PTP1B inhibitory potential of M. conica with an IC50 value of 26.5 μg/ml as compared to the positive control, oleanolic acid (IC50 36.2 μg/ml). In vivo investigation showed a gradual decrease in blood sugar level in M. conica-treated mice (132 mg/dl) at a concentration of 100 mg/kg as compared to diabetic mice (346 mg/dl). The extract positively improved liver and kidney damages as were shown by their serum glutamic pyruvic transaminase, serum glutamic oxaloacetate, alkaline phosphatase, serum creatinine and urea levels. Histopathological analysis revealed slight liver and pancreas improvement of mice treated with extract. Cytotoxicity assays displayed lower IC50 values. Based on the present results of the study, it may be inferred that M. conica are rich in bioactive compounds responsible for antidiabetic activity and this mushroom may be a potential source of antidiabetic drug. However, further studies are required in terms of isolation of bioactive compounds to validate the observed results.